2010
DOI: 10.1890/08-1773.1
|View full text |Cite
|
Sign up to set email alerts
|

Small‐mammal seed predation limits the recruitment and abundance of two perennial grassland forbs

Abstract: Although post-dispersal seed predators are common and often reduce seed density, their influence on plant population abundance remains unclear. On the one hand, increasing evidence suggests that many plant populations are seed limited, implying that seed predators could reduce plant abundance. On the other hand,.it is generally uncertain whether the magnitude of seed limitation imposed by granivores is strong enough to overcome density-dependent processes that could compensate for seed loss at later stages. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 31 publications
3
113
0
Order By: Relevance
“…Hulme (1998) commented that few studies had quantified predation from multiple guilds of seed predators, particularly in the tropics, and in general the dearth of field experiments that also monitored subsequent seedling dynamics (e.g., Schupp and Fuentes 1995, Curran and Webb 2000, Bricker et al 2010. At Korup we demonstrated that Microberlinia died faster than Tetraberlinia, and both species survived best when protected from small mammals in gaps (Fig.…”
Section: Seedling Dynamics and Herbivorymentioning
confidence: 77%
See 2 more Smart Citations
“…Hulme (1998) commented that few studies had quantified predation from multiple guilds of seed predators, particularly in the tropics, and in general the dearth of field experiments that also monitored subsequent seedling dynamics (e.g., Schupp and Fuentes 1995, Curran and Webb 2000, Bricker et al 2010. At Korup we demonstrated that Microberlinia died faster than Tetraberlinia, and both species survived best when protected from small mammals in gaps (Fig.…”
Section: Seedling Dynamics and Herbivorymentioning
confidence: 77%
“…Invertebrate predation, however, did not fully offset increased seedling establishment of Microberlinia in exclosures. Not unlike forbs in grasslands (Bricker et al 2010 [Green and Newbery 2002]). A similar ''enemy-replacement'' phenomenon, but greater in severity, was reported from another African rain forest where 84% of mast seeds of the mono-dominant Gilbertiodendron dewevrei (Caesalpiniaceae) protected against small mammals were killed by specialist curculionid beetles (Hart 1995;also see Hall 2008).…”
Section: Effects Of Canopy Cover On Predationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some further examples of epizoochory are found in the genera Lappula (Ridley, 1930) and Cryptantha, the latter possessing small nutlets and rough sculpturing, which are easily detached from the plant (Carlquist, 1983;Grau, 1983;Hasenstab-Lehman and Simpson, 2012). Endozoochory is typical in Lithospermum L., whose stone-like nutlets are swallowed by granivorous birds, passing intact through their guts and germinating successfully later on (Van der Pijl, 1982;Best and Smartt, 1986;Bricker et al, 2010;Selvi et al, 2011;Weigend et al, 2016). In this genus the occurrence of barochory has also been shown (Selvi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining the effect of post-dispersal seed predation on two perennial forbs in a grassland, granivores such as Peromyscus maniculatus, were found to be the primary driver for differences in plant abundance in and out of small mammal exclosures (Bricker et al, 2010). The granivores were able to lower the plant abundance outside of the small mammal exclosures in this grassland habitat, which adds to similar work in desert and coastal dunes systems (Bricker et al, 2010).…”
Section: Introductionmentioning
confidence: 85%